INFLUENCE OF VAPORIZATION AND IMPREGNATION OF SILVER NANOPARTICLES ON THE DRYING RATE OF Eucalyptus pellita F. MUELL. - Pace, José Henrique Camargo; Latorraca, João Vicente de Figueiredo; Carvalho, Alexandre Monteiro; Santos, Glaycianne Christine Vieira dos; Almeida, Sabrina Mayer de; Gomes, Fernando José Borges (Floresta, 2019)
The aim of this study was to evaluate the effect of vaporization and impregnation of silver nanoparticles on the Eucalyptus pellita wood properties. For that, samples of three radial regions of the wood from three trees were vaporized for 12 and 24 hours and later on, they were immersed in solution of silver nanoparticles with and without application of vacuum (750 mm.Hg). Anatomical, physical and chemical analyzes of the wood were carried out in order to evaluate the effect of the treatments. The drying rate of the wood was determined in moisture bands before and after the fiber saturation point. Generally, the treatments did not modify the anatomical characteristics, permeability, and wood density in the three radial regions; however, the vaporization for 24h reduced the total extractive content in the wood. These results contributed in obtaining gains in the drying rate before and after the fiber saturation point. The effect of impregnation of nanoparticles with vacuum preceded by two periods of vaporization resulted in higher drying rates and the time of 24h stood out, resulting in the best averages among all treatments. The impregnation of nanoparticles had positive effects on the drying rate.